2016
DOI: 10.18632/oncotarget.9258
|View full text |Cite
|
Sign up to set email alerts
|

PRRT2 mutations lead to neuronal dysfunction and neurodevelopmental defects

Abstract: Mutations in the proline-rich transmembrane protein 2 (PRRT2) gene cause a wide spectrum of neurological diseases, ranging from paroxysmal kinesigenic dyskinesia (PKD) to mental retardation and epilepsy. Previously, seven PKD-related PRRT2 heterozygous mutations were identified in the Taiwanese population: P91QfsX, E199X, S202HfsX, R217PfsX, R217EfsX, R240X and R308C. This study aimed to investigate the disease-causing mechanisms of these PRRT2 mutations. We first documented that Prrt2 was localized at the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 40 publications
7
65
0
Order By: Relevance
“…Its temporal expression increases during the development and in fact PRRT2 silencing in primary neurons decreases synaptic density and alters nerve terminal ultrastructure. Using RNA interference, it has been shown that knocking PRRT2 in mouse embryos leads to a delay in neuronal migration and defects in synaptic development [45]. Therefore, it is not surprising that homo- or heterozygous biallelic PRRT2 mutations can lead to neurodevelopmental disorders [4648].…”
Section: A Pathophysiological Frameworkmentioning
confidence: 99%
“…Its temporal expression increases during the development and in fact PRRT2 silencing in primary neurons decreases synaptic density and alters nerve terminal ultrastructure. Using RNA interference, it has been shown that knocking PRRT2 in mouse embryos leads to a delay in neuronal migration and defects in synaptic development [45]. Therefore, it is not surprising that homo- or heterozygous biallelic PRRT2 mutations can lead to neurodevelopmental disorders [4648].…”
Section: A Pathophysiological Frameworkmentioning
confidence: 99%
“…Seizure disorders associated with many of these newly identified mutations manifest in early childhood and are accompanied by serious behavioral comorbidities: SYN1 (Giannandrea et al, 2013; Paemka et al, 2013), STXBP1 (Stamberger et al, 2016), Prrt2 (Liu et al, 2016; Valente et al, 2016), NAPB (Conroy et al, 2016), SV2a. (Serajee and Huq, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was performed according to a previous report . Briefly, HEK293T human embryonic kidney cells were cultured in Dulbecco modified Eagle medium (Life Technologies) with 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
“…Most truncating variants of PRRT2 lead to a shortened protein that lacks both C‐terminal TM domains. Previous functional studies have confirmed that truncated PRRT2 failed to localize to the plasma membrane and distributed in the cytoplasm and sometimes in the nucleus . Thus, mislocalization of PRRT2 mutations may lead to the loss of its normal functions at the synapses .…”
Section: Introductionmentioning
confidence: 96%